Fostering Excellence: Innovating The On-The-Job Training Program At Bisu-Main Campus College Of Business, Arts, And Sciences (Journal of Namibian Studies : History Politics Culture, 2022)
The realm of on-the-job training is complex and multifaceted, necessitating meticulous management and consideration of numerous factors. From curriculum design to real-world implementation, each facet plays an integral role in shaping the effectiveness of the training program. As such, the synthesis of theoretical knowledge and practical application remains paramount, ensuring that students not only meet academic requirements but also emerge as adept professionals poised to excel in their respective career paths. The objective of the study was to investigate the traits, performance, advantages, and challenges faced by On-The-Job Trainees (OJTs) in the College of Business, Arts, and Sciences at BISU-Main Campus. Specifically, it aimed to ascertain the demographic profile, characteristics, performance, and perceptions of OJTs, focusing on their orientation, benefits, and challenges. Additionally, the study aimed to determine any potential connections between OJTs' characteristics and performance, as well as their training experience and work performance. The research employed a mixed method, utilizing a self-made questionnaire as the data collection instrument. Respondents were OJTs enrolled in Bachelor of Science programs in Psychology, Tourism, and Office System Management. The findings revealed that both in-campus and off-campus OJTs strongly agreed on their work attitude. Both groups strongly agreed on the personality trait of self-confidence, with slightly higher agreement among off-campus OJTs. Perception of training experiences was rated as very good for off-campus OJTs and good for in-campus OJTs.  Both groups rated the training evaluation as good with slight variation between in-campus and off-campus OJTs. Tasks unrelated to the course received positive ratings, with off-campus and in-campus OJTs both indicating good. In terms of benefits, in-campus OJTs rated it as poor while off-campus OJTs rated it as fair. Challenges encountered received poor for in-campus and fair for off-campus OJTs. The overall weighted mean was lower for in-campus than off-campus, both categorized as fair. There is no significant relationship was observed between OJT characteristics and perceptions regarding training experience and OJT performance.